PENGARUH BRAND AMBASSADOR DAN SOCIAL MEDIA MARKETING TERHADAP KEPUTUSAN PEMBELIAN BRAND NPURE DENGAN KEPERCAYAAN KONSUMEN SEBAGAI VARIABEL MEDIASI DI SURABAYA - Nur Amalia; Dewi Nuraini (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The purpose of this study is to determine the influence of Brand Ambassador and Social Media Marketing on Purchase Decisions of the NPURE brand, with Consumer Trust as a mediating variable among consumers who use NPURE products in the city of Surabaya. This research was conducted on NPURE brand consumers in Surabaya, with a sample size determined to be 100 respondents. Data collection was carried out through the distribution of questionnaires via Google Forms indirectly through social media. The data analysis technique used is the SEM-PLS method. Based on the analysis results, it was found that Brand Ambassador has a significant influence on Consumer Trust, Social Media Marketing has a significant influence on Consumer Trust, Consumer Trust has a significant influence on Purchase Decisions, Brand Ambassador has a significant influence on Purchase Decisions, Social Media Marketing has a significant influence on Purchase Decisions, Brand Ambassador has a significant influence on Purchase Decisions through Consumer Trust, and Social Media Marketing has a significant influence on Purchase Decisions through Consumer Trust.